2012
DOI: 10.4081/ejh.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

How physical exercise changes rat myotendinous junctions: an ultrastructural study

Abstract: Myotendinous junctions (MTJ) can be easily injured by overloading or trauma, and exercise training may be a way of increasing their resistance to mechanical stress. To this end, we examined herein the morphological changes induced by moderate exercise training in the MTJ of extensor digitorum longus (EDL) and gastrocnemius muscles in rats. Twelve Sprague-Dawley rats were used in this investigation. Six of them were trained to run on a treadmill for 1 h/day, 3 days/week over 10 weeks in order for them to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 36 publications
4
41
2
Order By: Relevance
“…In addition, it is thought that the meshwork formed by the branching and subsequent joining of the processes is important for regulating tension. 8,41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is thought that the meshwork formed by the branching and subsequent joining of the processes is important for regulating tension. 8,41 …”
Section: Discussionmentioning
confidence: 99%
“…A moderate treadmill-running regimen applied to rats increased the percentage of the branched tendon interdigitations at the MTJ and the number of bifurcations of the digit-like processes. 8 …”
Section: Introductionmentioning
confidence: 99%
“…66-72 Here too, the unusual localization or translocation of specific proteins was considered as an important evidence, 72 all the more so as it occurs under pathological conditions ( e.g ., in myotonic dystrophy) or in sarcopenia, i.e ., the loss of muscle mass and function physiologically occurring in the aging process. 67,76,77 As demonstrated by ultrastructural immunocytochemistry, the dystrophic phenotype would depend on a general alteration in the post-transcriptional maturation of pre-mRNAs. Interestingly, the accumulation of pre-mRNA processing factors in the myonuclei of dystrophic patients is reminiscent of the nuclear alterations found in age-related sarcopenia.…”
Section: Histochemistry and Cytochemistry In Recent Literaturementioning
confidence: 99%
“…The effect of physical exercise on the structural features of skeletal muscle cells (both myocytes and satellite cells) has repeatedly been investigated, 75,76 but so far much less attention has been paid to the consequence of exercise on the myotendineous junction: 77,78 Molecular and ultrastructural analyses demonstrated that the myotendineous junction is able to adapt to increased tensile forces by enlarging the muscle-tendon contact area, thus increasing mechanical resistance.…”
Section: Histochemistry and Cytochemistry In Recent Literaturementioning
confidence: 99%
“…The mechanisms underlying age-related skeletal muscle wasting and weakness are probably manifold and still remain to be fully elucidated; 30 however, although no specific therapy is presently available to counteract its onset or progress, studies performed on humans and other mammals have stressed the importance of physical exercise as an effective, although still debated, approach to prevent or limit the age-related muscle mass loss. 3236 …”
Section: Skeletal Muscle Features In Sarcopeniamentioning
confidence: 99%